Odpowiedź:
a)
1/3x - 2 = x + 2
1/3x -x = 2 + 2
-2/3x = 4 /:(2/3)
x = 4/1*(-3/2)
x = -6
b)
1 - 6/7x = 4/7 /*7
7 - 6x = 4
-6x = 4 - 7
-3x = -3
-6x = -3 /:(-6)
x = 1/2
c)
6(1/4x - 2) = 18 /:6
1/4x - 2 = 3
1/4x - 2 = 12 /*4
x - 8 = 12
x = 12 + 8
x = 20
d)
x/6 - 1/6 = 1 /*6
x - 1 = 6
x = 7
e)
-2(2x - 1) = x/3
-4x + 2 = x/3 /*3
-12x + 6 = x
-13x = -6 /:(-13)
x = 6/13
f)
2/5(3 - x) = -2 /*5/2
3 - x = -5
-x = -5 - 3
-x = -8
x = 8
g)
3/4(2 - 3x) = -6 /*4/3
2 - 3x = -8
- 3x = - 10 /:(-3)
x = 10/3
x = 3 1/3
h)
1/5(x - 3) = 9 - x /*5
x - 3 = 45 - 5x
x + 5x = 45 + 3
6x = 48 /:6
x = 8
i)
3/5 + x
----------- = x + 1 / * 2
2
3/5 + x = 2x + 2
x - 2x = 2 - 3/5
-x = 1 2/5
x = 1 2/5
Moge Naj?